Pengaruh Terapi Bekam Kering Terhadap Tekanan Darah Pada Ibu Preeklampsia Postpartum - Yayuk Eliyana; Mukhamad Nooryanto; Sri Poeranto (JURNAL INFO KESEHATAN, 2019)
Preeclampsia during pregnancy can persist in the postpartum period and usually returns to normal in the first week of postpartum. The overall incidence of preeclampsia or postpartum hypertension is around 57.1%. Non-pharmacological techniques to treat hypertension have been developed, one of which is dry cupping as an option to reduce blood pressure. Research on Quasy experiment with non-equivalent control group design. Research location at Dr. Saiful Anwar Malang HOSPITAL. The research time begins in August-September 2018. The population in this study is 34 preeclampsia postpartum mother with systolic blood pressure criteria of at least 140 mmHg and has obtained previous MgSO4 therapy. The research samples consisted of 17 samples on the treatment group and 17 samples in the control group. Sampling techniques using consecutive sampling. The independent variable of this research is dry cupping therapy, while the dependent variable is blood pressure. Test statistics are used paired T test and Wilcoxon test to analyze the difference before and after treatment. Independent test of the T-Test sample and Mann Whitney test to analyse the difference between the two groups. Different test results with the Wilcoxon test obtained p-value on systolic and diastolic blood pressure smaller than the significance level α = 0.05, it can be concluded that there were significant differences in postpartum maternal blood pressure with preeclampsia before and after given dry cupping therapy and therapy standard. The results of Mann Whitney's analysis obtained data that there were significant differences in the difference in systolic blood pressure between groups given standard therapy and groups given standard therapy plus dry cupping therapy. Based on the results of these studies, dry cupping therapy can be used as a companion therapy to reduce blood pressure in postpartum mothers with preeclampsia.